(untitled) (Journal of the College of Education for Women, 2019)
AI-Shidyaq is considering one of the scholars’ of Arab modern Renaissance. Heenjoyed a dusting nished status among the men of letters of his age. He added many things inlanguage and literature that made him, during the Arab modern Renaissance, a pioneerresearcher in the 1900s. He had established a state for literature that turnal him in to one ofthe critics of his age, to the extent that he was called the Eagle of Lebanon (similar to theEagle of Quraish).He was also called the Jahiz of his age, Voltaire of his generation and Khleel of the1900s. He was also called Victor Hugo.He was characterized by a character of smoothness in style, Clarity in meaning andpurpose, an ability to analyze, Describe and write prose and poetry, He was so brilliant inlangrage, Rebetorics and grammar. That why he attracted many powerful people.He participated in spreading Arabia culture by teaching Arabic in European schools andcompiling many books in different specializations. Al-Jawaeb printing house, Which wasfounded by Al-Shidyaq, One of the most famous institutions in Islamic Arab culture in thenineteenth century. it contributed in printer and publishing many masterpieces of Arabheritage. Accordingly, many oriantalists praised the great role played by Ah-Shidyaq at thattime. He was dissented by orient list and historian (Gibb) as "one of the great heroes whodefend lslam". The death of Al-Shidyaq was considered a great loss, not only to our Arabhome lard but also to the whole world. This can be proved by his burial, which was attendedby many great scholars and wails’. Besides, his memory is still present up to now, for he isreferred to as one of the pioneers of modern Arab Renaissance.